Mobile application for life long learning - Tan, Li Wen (Nanyang Technological University, 2020)
With the advancement of technologies, more processes have been digitized to improve user experience. Some examples are online banking, online shopping and online learning platforms. Online learning platforms are becoming increasingly popular due to its convenient and flexible nature. It is time effective as it allows the user to go through the materials at their own comfortable pace, eliminating restrictions to that of a traditional classroom setting. In addition, it provides the ease of accessibility, affordability, stability and diversity of learning materials online through portable gadgets like mobile devices. The numerous benefits to online learning platform are the motivation behind this Final Year Project – the development of life long learning mobile application platform to encourage lifelong learning and independent learning attitude.